RELAY™ Branched device: The story of an aortic arch device. Issue 11 (19th September 2022) - Al‐Tawil, Mohammed; Ammari, Leen; Mohammed, Idhrees
Abstract: Background: The management of aortic arch pathologies represents a great challenge and is associated with high rates of mortality and morbidity. The invasive and radical open surgical repair (OSR) is the standard of care for this group of patients. A superior endovascular approach via thoracic endovascular aortic repair (TEVAR) has been introduced to treat arch pathologies with specifically designed endografts. This approach was shown to benefit patients who are deemed "high risk" for undergoing OSR as it is a greatly less invasiveness option and thus, yields lower rates of morbidity and mortality. Aims: This commentary aims to discuss the recent study by Tan and colleagues,  which reports original data on the neurological outcomes after endovascular repair of the aortic arch using the RELAY™ Branched device. Methods: We carried out a literature search on multiple electronic databases, including PubMed, Ovid, Google Scholar, Scopus, and EMBASE, to collate research evidence on the neurological outcomes of endovascular aortic arch repair with TEVAR. Results: Tan and colleagues showed through their original clinical data that the RELAY™ Branched device has a high rate of technical success and favorable neurological outcomes. There were no reported neurological deficits in patients who received the triple‐branched RELAY™ Branched device. Conclusion: The RELAY™ branched endograft is well‐established for candidates for aortic arch endovascular repair with favorable neurological outcomes. Multiple considerations can help control the incidence of stroke following endovascular repair. These include optimization of the supra‐aortic vessels' revascularization, weighting the embolic risk in patients with atheromatous disease, and careful preoperative assessment to select the best candidates for arch endovascular repair.